Social differentiation in the Richtersveld, a Namaqualand rural area - Boonzaier, Emile André (Social Anthropology, 2026)
This dissertation addresses the issue of ru..:.·ul differentiation in the Richtersveld Reserve 1 a Rural Coloured Area in the NorthWestern Cape. Rural differentiation is seen as being a function of the important but variable relatj_onship between far.ming activity and oscillating labour miqration. By focusing on two-dif£erant settlements in the Richtersveld - Kuboes and Ekst.eer!fontein - the variable nc>tu:ce of the -relationship oetweon fa,~ming 2.nd labour TfLl.gration is emphasised, More lmporU1.ntly, however, it is ,3.rgucd, on U1e b.:-..sis of statistical and other evidence, tJ1at the d:i ££ercntial involvement of people domiciled ln the Richb::1x::;veld if far.r.,.ing and mJ.lj"Cc:!1t labour cannot be accounted for only in ter.rl:3 of the. c,t~V~lopmenl:al cycle of umr,2.:;ti,.:: s,:·oups. Si:llr1i.<,~:3 ,.,hich larve c.c.1.keJ1 ~n:.r::h a vii:w (Murray, 1976 ,:!:-J<J F:pieqel, 1979) h,:.ve Leen li.rnit:2d by a ~;hort-t.errn per.s!1~cti ?e wl1ich deals 11ii th sp~r .. i. fie procE:sses at the lcr:al level, but -;,,.-:lich ove1.·look(~ processes of l.i.ncaJ. s,~,cL:il cbZtnge. r1 taking a 1ongtir ti;1i..-:- perspecu.~,e, I ha,,·e souCJht:::. to a1:gu2 ~har. the r-el2.tions"i1 i.p 08 twr:f>n f.::i.:c.,•.J.ng end ~;_ ',;i1·a.,1i., l;;,bot::r :!..n tile Ri<.:;H•c .... ·sveld has un1..~e:;:,:J':•nE. d dj;·:c:·:-)·1:rd.hl1~ chang2 wr1J.d1 has given cise -::o the fc-rnatiO' ·. 0.?. ,;pec:L:C.i.c soci~-1 l cl ,,5.'iCS. increasingly ~- -==com<:: C'.0iK: _o t:t~- l.'.ecl i.n th-2 ha.nds of ;;J. few wealthy fa:i:Trrer ~, ';thil•.:.1 the n~:;t. c,f :.i1e p,:1_J1.!.laUon h:.:is turned more and r.lore to migrant. lt1.bour: zi.s t.heLr .;.;ol e :,8lll".'C~ of jncorne. ii. The specific :iature of farming in the Richt,"."sveld today and ci1e barriers facing the p~ospective farmer wishing to build up his herd, as well as the political strategiP.s of the wealthy farmers, are a.11 .see~·l as significa~t elemen·ts in the process of rural differ~ntiation in the Richtersveld. I also make some attempt to trace the hi.stor:i.cal dev0lopments which might have influenced this pattern. I~ particular, I focus on the historical development of gr:01.:p id3nti ties ,--:.nd the way i::1 whj_ch the consciousnsss associ.::itcd with ttem !!light be seen to have given rise to the fc:cm,:i.ti0n of social classes. Finally, the pro~(;SS o( .--:·ur'J.l diffr~r2.i7_'._:i.ati.ntl is viewed in terms of the specific ~f<WerrLLi:2,it pol i_cy ;._js i. i: pe;:.::ains to Uie Rural Colom::,:d A'l:eas ;-~·,1.d it is s u,;ges tGd tho~ the obsei: ve-d t c2nds A1~E.! in line with t.h .. · r-n::::.r:.r der..ui;tds for skj J. -!.ed ,ind c?:.-:.-mt··ski l led labour .in t.he N,~ .'.'.d~l,.tl a11d r,;::gion as a whole.